PENGARUH JENIS MULSA ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Dahlia Rumakuway; Frederick J Rumahlatu; Marlita H Makaruku (Universitas Pattimura, 2016)
The study aimed to determine the right type of organic mulch on the growth and production of mustard plants that included plant height, number of leaves, leaf area, shoot fresh weight root fresh weight, shoot dry weight and root dry weight. A completely randomized design was applied in the experiment using organic mulch as a treatment consisting of control, alang-alang leaves, gamal leaves and lamtoro leaves. The results showed that treatment without mulch (control) gave the highest values on all parameters and the lowest was in the treatment of gamal leaves mulch. Mulch of lamtoro leaves indicated the highest fresh weight of shoot compared to the use of alang-alang leaves and gamal leaves.